2021
DOI: 10.5194/bg-18-1971-2021
|View full text |Cite
|
Sign up to set email alerts
|

Improving the monitoring of deciduous broadleaf phenology using the Geostationary Operational Environmental Satellite (GOES) 16 and 17

Abstract: Abstract. Monitoring leaf phenology tracks the progression of climate change and seasonal variations in a variety of organismal and ecosystem processes. Networks of finite-scale remote sensing, such as the PhenoCam network, provide valuable information on phenological state at high temporal resolution, but they have limited coverage. Satellite-based data with lower temporal resolution have primarily been used to more broadly measure phenology (e.g., 16 d MODIS normalized difference vegetation index (NDVI) prod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Observations from geostationary satellites have much higher effectiveness than MODIS data to track the seasonality of vegetation growth and phenology detections [39,40,43,66]. As revealed in the previous studies, cloud contaminations are the major impacts on the quality of EVI2 time series for phenology detections [16,36].…”
Section: Discussionmentioning
confidence: 87%
“…Observations from geostationary satellites have much higher effectiveness than MODIS data to track the seasonality of vegetation growth and phenology detections [39,40,43,66]. As revealed in the previous studies, cloud contaminations are the major impacts on the quality of EVI2 time series for phenology detections [16,36].…”
Section: Discussionmentioning
confidence: 87%
“…Progress in geostationary satellite systems offers critical advantages of monitoring specific locations over extended time frames and different times of the day, which becomes especially important for regions unreachable by frequent field surveys or ground‐based phenological observation networks (Hashimoto et al, 2021; Wheeler & Dietze, 2021). For example, the application of GOES Advanced Baseline Imager over Amazon tropical forests (Hashimoto et al, 2021) revealed presence of seasonality in 85% of the region's evergreen forests, which would not be possible to detect with traditional sun‐synchronous sensing.…”
Section: Caveats and Opportunities In Phenological Estimationmentioning
confidence: 99%
“…Geostationary systems can also substantially reduce the impact of clouds on estimation of phenological transition dates and improve the assessments of phenological trends and shifts over vast regions and multi‐year periods. To better understand potential uncertainties due to still coarse spatial resolutions (~1 km) of such products, their time series can be cross‐compared with high frequency in situ observations such as phenocam images (Wheeler & Dietze, 2021).…”
Section: Caveats and Opportunities In Phenological Estimationmentioning
confidence: 99%
“…In addition, because they provide a synoptic view over multiple decades, satellite‐derived phenology metrics can also be used to track changes in plant seasonality (Zeng et al, 2011), which allows us to determine the controls of plant seasonality on carbon cycling and storage (Pulliainen et al, 2017; Richardson et al, 2010; Zhu et al, 2013). More recently, the characterization of vegetation phenology has become more routine, particularly with the creation of standard data products (Ganguly et al, 2010), while novel platforms now enable higher temporal resolutions (Wheeler & Dietze, 2021). Similarly, biophysical products, including LAI, are often used to capture seasonality of plants, but also provide a more meaningful metric for evaluating carbon cycle models (Li et al, 2018; Viskari et al, 2015).…”
Section: The Importance Of Phenology For Capturing Carbon Fluxesmentioning
confidence: 99%